PERBANDINGAN RETURN SAHAM BANK BUMN SEBELUM DAN SESUDAH PENGUMUMAN PANDEMI COVID-19 DI INDONESIA - Dewi Maya Sari; Meutia Handayani; Nadifah Tasya (Jurnal Penelitian Ekonomi Akuntansi, 2022)
This study aims to analyze the comparison of stock returns of state-owned banks listed on the Indonesia Stock Exchange before and after the announcement of the Covid-19 pandemic. The data used is the weekly closing stock price of state-owned banks for the period January-February (before) and March-April (after). This research is a type of quantitative research with quantitative descriptive analysis method. Data collection techniques using the census method. The results showed that the stock returns of state-owned banks listed on the Indonesia Stock Exchange fluctuated in the period before and after the announcement of the Covid-19 pandemic